THE INFLUENCE OF COMPANY DEBT AND PROFITABILITY ON COMPANY VALUE WITH PRODUCT QUALITIY AS A MODERATING VARIABLE - Indah Oktari Wijayanti; Listiana Sri Mulatsih; Loso Judijanto; Nurchayati Nurchayati; Yahya Yahya (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract Good company values are the aspiration of a company to have a good image and be able to help the country, employees and local residents. Because the company values are good, everyone will experience prosperity. There are a number of factors that can influence a company, including a measurable debt policy and adequate profits so that they can help the company in difficulties and fund the company's large projects. Therefore, this research aims to analyze the influence of Company Debt and Profitability on Company Value. Different from previous studies, this research adds the Product Quality variable as a moderating variable. This research is a quantitative research with an explantory approach. The data used in this research is secondary data which was distributed through a questionnaire method to the Head of Finance and Employees in the Kuangan field at PT. Sawit Lestari Group Benkgukulu, Pt. Sumber Andalas Kencana, PT. Sawit Sumbermas, and PT. Astra Agra Palm Oil which is spread throughout Indonesia. The data used was analyzed with Smart PLS 3.0. The results show that the Corporate Debt and Profitability variables have a positive relationship and have a significant influence on the Company Value variable because each variable has a t-table value below the significance level of 0.05. Apart from that, the Product Quality variable can significantly moderate the influence of the Corporate Debt and Profitability variables on Company Value. Keywords : Company Debt, Profitability, Product Qualitiy, Company Value